A political practice of occupational therapy - Pollard, Nick, MSc(OT); Sakellariou, Dikaios; Kronenberg, Frank (Churchill Livingstone/Elsevier, 2009)
This challenging and innovative book explores the political aspects of occupational therapy. It looks at how practitioners may develop political awareness in order to aid community development. A Political Practice of Occupational Therapy is about maximizing the potential impact of occupational therapists' engagements and ensuring the profession is working towards the contruction of a civic society. It is supported by twelve chapters of practice examples from the UK, US, Georgia and Australia, as well as a history of the profession as an agency for social change.